2020
DOI: 10.37869/ijatec.v1i1.12
|View full text |Cite
|
Sign up to set email alerts
|

The Regression Models of Impact Strength of Coir Coconut Fiber Reinforced Resin Matrix Composite Materials

Abstract: The need of coconuts in Indonesia is relatively high. The use of large quantities of coconuts produces large amounts of organic waste from coco fiber, which tends to become waste if it is not used to be beneficial for humans.One of the potential uses of coconut fiber is as a reinforcement of natural fibers in polymer matrix composite materials. Recently, the applications of composite materials have been expanded widely including structural angine component which whitstand certain load like impact load. But mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Research on the effect of oil palm fiber content on the axial load fatigue cycle on resin matrix composite has been conducted. That study obtained that The impact strength of the composite material is influenced by the fiber length and fiber content [16] [12]. Other researchers, who examined the effect of weight percentage on the tensile strength and flexure of coconut coir polyester fiber composites found that the percentage of 15% fiber weight has the highest average tensile strength of 24.478 MPa compared to 5% and 10% fiber fractions [17].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Research on the effect of oil palm fiber content on the axial load fatigue cycle on resin matrix composite has been conducted. That study obtained that The impact strength of the composite material is influenced by the fiber length and fiber content [16] [12]. Other researchers, who examined the effect of weight percentage on the tensile strength and flexure of coconut coir polyester fiber composites found that the percentage of 15% fiber weight has the highest average tensile strength of 24.478 MPa compared to 5% and 10% fiber fractions [17].…”
Section: Introductionmentioning
confidence: 88%
“…From this study, it was found that the highest impact strength was obtained in specimens with 10% weight fiber content compared to 5% and 7%. Regarding fiber length, it was found that the highest impact strength was obtained in specimens with a fiber length of 10 mm compared to the fiber length of 5 mm and 7 mm [16,17].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Polypropylene is widely used in injection molding processes using natural fibers [14,15,16,17]. Oil palm fiber have been studied extensively for the production of composites for various applications, such as, cement boards [18], energy absorption applications [19], concrete beam [20], as glass fiber substitutes [21] and also for automotive parts [22,23]. The effect of oil palm shell (OPS) powder on the mechanical performance and thermal stability of polyester composites were investigated by other researcher [24].…”
Section: Process Technologymentioning
confidence: 99%
“…The research regarding the influence of coconut coir fiber length and content on the impact strength of resin matrix composite has been investigated [24], The research obtained that the highest impact strength 2.78kJ/m 2 of composite specimens from 1.8% fiber content with 8mm fiber length, whereas the lowest impact strength of 0.75kJ/m 2, resulted from 1.8% fiber content with 10mm fiber length.…”
Section: Introductionmentioning
confidence: 99%